PROBLEMS OF DETERMINING THE BOUNDARIES OF THE SUBURBAN AREA OF THE LARGEST CITIES OF UKRAINE - Мykhidenko М. (Municipal economy of cities. Series: «Economy science», 2024)
The article examines a relatively recent concept used in regulatory documents, known as the largest cities in Ukraine. Unfortunately, statistical data on the population size has not been kept in Ukraine for a long time, which makes it challenging to conduct the research in the most detailed and in-depth manner. Despite this, the study used data from enterprises and industries, cartographic data, and field surveys. It allowed us to identify seven potentially largest cities: Kyiv, Kharkiv, Odesa, Dnipro, Donetsk, Lviv, and Zaporizhzhia. The authors studied the concept of suburban areas in detail and found differences between different classes of suburban areas. We used works from various scientific fields: geographical, economic, sociological, legal, and urban planning, which makes this article interdisciplinary. Also, we considered the regulatory legal documents of the State Building Code, the Laws of Ukraine, and historical materials. The cities of this study tend to grow and spread geographically throughout the area, signalling us to revise previously accepted interpretations and norms of suburban areas. It led us to conduct the study and adopt a new definition of the suburban area of the largest city. Therefore, the ‘suburban area of the largest city’ is the territory located outside the largest city along transport and motorways and providing close partnership with the city in economic, environmental, recreational, cultural, labour, scientific, and other areas. The article considers the modern problems of the suburbs, such as territorial conflicts on the appropriation of land, conflicts on the use of territories not for their intended purpose, and clashes between developers of the residential sector, enterprises, and the ecological framework. In the latter, the natural flora and fauna system suffers the most. External factors also influence the slowdown of suburban development: military conflicts, instability of foreign policy, economic decline, and others. To prevent such a scenario, we have defined the goals and objectives of the suburbs. In the current situation in Ukraine, this study can help to facilitate further research on the development of territories.